2018
DOI: 10.1093/pasj/psy087
|View full text |Cite
|
Sign up to set email alerts
|

A high dust emissivity index β for a CO-faint galaxy in a filamentary Lyα nebula at z = 3.1

Abstract: We present CO J = 4 − 3 line and 3 mm dust continuum observations of a 100 kpcscale filamentary Lyα nebula (SSA22 LAB18) at z = 3.1 using the Atacama Large Millimeter/submillimeter Array (ALMA). We detected the CO J = 4 − 3 line at a systemic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
6
4
0
Order By: Relevance
“…This might be in line with recent results reporting steeper values in > 3 galaxies (e.g. Kato et al 2018;Jin et al 2019;Casey et al in prep. ), suggesting an evolution of the dust emissivity index with redshift and/or luminosity.…”
Section: On the Nature Of Non-detectionssupporting
confidence: 92%
“…This might be in line with recent results reporting steeper values in > 3 galaxies (e.g. Kato et al 2018;Jin et al 2019;Casey et al in prep. ), suggesting an evolution of the dust emissivity index with redshift and/or luminosity.…”
Section: On the Nature Of Non-detectionssupporting
confidence: 92%
“…With our sample we not only confirm this value to be a reasonable average value for highredshift dusty star-forming galaxies (β ; 1.5-2 is often assumed when modeling sources at both low and high redshift; e.g., Scoville et al 2016;Galliano et al 2018) but also show that there can be significant variation from galaxy to galaxy. We note that the recent ALMA measurement of β = 2.3 in a z = 3.1 galaxy by Kato et al (2018) is entirely consistent with the range of values we find for our SMGs, and therefore that source is not necessarily an outlier in dust properties. The recent sample of 47 SMGs from Birkin et al (2021) yields β = 2.1 ± 0.1, consistent with our results (J. Birkin, private communication).…”
Section: Comparison With Other Measurements and Theoretical Predictionssupporting
confidence: 91%
“…We find β = 2.7 ± 0.4 and T = 7.2 ± 1.1, with χ 2 = 2.31 and 1 degree of freedom, the probability to exceed (χ 2 ) due to noise alone is 0.128. This value of β is higher than perhaps expected (Draine & Lee 1984), although β > 2 has been found (e.g Kato et al 2018), and even β > 3 have been found (e.g. references within Shetty et al 2009).…”
Section: C1 Pressure Profile Fitting and Resultsmentioning
confidence: 59%
“…references within Shetty et al 2009). As in Kato et al (2018), source blending may also affect our Herschel photometry.…”
mentioning
confidence: 98%